2016
DOI: 10.1002/ps.4322
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of sublethal exposure to insecticide on the survivorship and mobility ofHalyomorpha halys(Hemiptera: Pentatomidae)

Abstract: Many insecticide-exposed H. halys adults retained significant mobility and flight capacity, with flight most pronounced immediately after exposure. These results suggest that brief exposure periods to efficacious insecticides will result in high dispersal and low mortality. Therefore, management strategies that enhance the retention of H. halys on insecticide-coated surfaces should be considered to ensure that adults are exposed to a lethal dose of insecticide. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…With regard to the LI, the values calculated in this work for different exposure times were comparable with those obtained in similar studies where different pyrethroids (e.g., bifenthrin) had been employed (Leskey, Lee, et al., ; Leskey, Wright, et al., ; Morrison et al., ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…With regard to the LI, the values calculated in this work for different exposure times were comparable with those obtained in similar studies where different pyrethroids (e.g., bifenthrin) had been employed (Leskey, Lee, et al., ; Leskey, Wright, et al., ; Morrison et al., ).…”
Section: Discussionsupporting
confidence: 84%
“…Pyrethroids are well‐known neurotoxic chemicals causing the uncoordinated movement of limbs, often followed by a complete loss of mobility without signs of activity and eventual death (Lee, Wright, et al., ; Leskey, Lee, et al., ; Leskey, Wright, et al., ). Nonetheless, the efficacy of α‐cypermethrin as a pesticide had never been investigated against H. halys, although pyrethroids (e.g., cypermethrin, cyhalothrin, cyfluthrin, bifenthrin) are considered among the most effective chemicals, not only against BMSB but also against pentatomids more generally (Lee, Wright, et al., ; Leskey, Lee, et al., ; Leskey, Wright, et al., ; Mooneyham et al., ; Morrison et al., , ; Nielsen et al., ; Willrich et al., ). Even if further specific trials are required to define standard levels of toxicity, our results showed that this compound has a strong insecticidal activity against BMSB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations